How Student’s Mental Health Affected During the COVID-19 Pandemic : A literature review - Satria Eureka Nurseskasatmata; Idola Perdana Sulistyoning Suharto; Eva Dwi Ramayanti; Endang Mei Yunalia (Journal for Quality in Public Health, 2020)
As the world continues to battle the day to day issues of the coronavirus pandemic, one aspect is the increasing problem of mental health for students. As schools have closed down and had suddenly transitioned to online classes. The model is currently the best alternative as keeping schools open poses a safety risk for students. Students with pre-existing mental health problems such as stress disorder, general anxiety disorder, post traumatic stress disorder, depression, or loneliness have become more vulnerable due to lockdown policies and showed itself in different ways. Lockdowns, travel restrictions, school closings and social/physical distancing have created a level of social isolation previously unseen across the globe. This upend, for many, can have profound consequences on one’s mental health. This paper aims to investigate the mental health status of student due to the policy response to Covid-19 Pandemic. The database searches used include Google Scholar, Research Gate, Science Direct, frontiersin, World Journal of Pharmaceutical and Medical Research. Keywords used in the search of the article was student, covid-19, mental health, epidemic, college by getting 19 articles and only 9 articles that were used through goal analysis, topic suitability , research methods used, sample size, the results of each article, and limitations that occur. This study found that mental health of college students is significantly affected when faced with a public health emergency. Student are likely to be experiencing stress, anxiety and depression. They need attention, help, and support from the community, family, and tertiary institutions. Therefore, the nurse need to consider planning for acute and long-term subsequent psychological interventions should focus on strengthening psychological counseling and emotional comfort for students through the involvement of counselors, psychologists. It is suggested that the mental health of college students should be monitored during epidemics.